A novel approach for the removal of chromium (VI) from aqueous solutions using nano iron oxide. Issue 13 (21st October 2022) - Gusain, Deepak; Verma, Vartika; Uma,; Bux, Faizal; Sharma, Yogesh C.
ABSTRACT: Synthesis of iron oxide was performed at different molar concentrations along with removal of chromium. The magnetite, maghemite and haematite mixture synthesised in all samples. Only Raman analysis deciphered the synthesis of haematite among all characterisation techniques applied. TEM image suggested the particles were round, irregular in shape and having size in the range of 16–18 nm. Chromium removal by synthesised nano-crystalline iron oxide/hydroxide was achieved by variation of pH (2–8), adsorbent dose (4–8 g/l), initial concentration of chromium (20–50 ppm) and temperature (30–40°C). Analysis of coefficient in regression equation for each factor suggests pH was most dominating factor (coefficient = – 43.52) followed by adsorbent dose (coefficient = 3.17) and concentration (coefficient = −3.01). Temperature did not significantly affect the adsorption process. Optimisation of the results (100% chromium removal) suggest optimum condition were at concentration 20 ppm, pH = 2–2.5 and adsorbent dose of 11 gm/l and 30°C.